1994
DOI: 10.1093/hmg/3.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ΓE-crystallin pseudogene in the human hereditary Coppock-like cataract

Abstract: The locus for the hereditary human Coppock-like cataract (CCL) is closely linked to a particular combination of polymorphic TaqI sites within the human gamma-crystallin gene cluster. Mapping of these sites shows that they define a 15 kb region encompassing the gamma D and psi gamma E gene. The gamma D and the psi gamma E gene were cloned from the CCL chromosome and characterized. The gamma D gene was functionally equivalent to its allele cloned from a wild-type chromosome. The CCL psi gamma E gene contains a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 0 publications
0
34
1
1
Order By: Relevance
“…These results contradict a common view of cataract formation, according to which protein unfolding or significant destabilization of the protein structure is a prerequisite for protein aggregation and cataract formation (30)(31)(32)(33)(34). An example of this view is the hereditary Coppock-like cataract, in which a truncated form of ␥E crystallin was believed to be overexpressed in the lens (3,33). Recent studies (30) now link this cataract to a mutation in the ␥C crystallin gene.…”
Section: Resultscontrasting
confidence: 65%
“…These results contradict a common view of cataract formation, according to which protein unfolding or significant destabilization of the protein structure is a prerequisite for protein aggregation and cataract formation (30)(31)(32)(33)(34). An example of this view is the hereditary Coppock-like cataract, in which a truncated form of ␥E crystallin was believed to be overexpressed in the lens (3,33). Recent studies (30) now link this cataract to a mutation in the ␥C crystallin gene.…”
Section: Resultscontrasting
confidence: 65%
“…A putative pathological mutation has been described in a ''gene'' encoding a paternally expressed antisense transcript of the GNAS complex locus (GNASAS; MIM] 610540) [Bastepe et al, 2005], whereas a functional polymorphism has been reported within an enhancer at the 3 0 end of the CDKN2BAS ''gene'' (MIM] 600431), which encodes an antisense RNA transcript [Jarinova et al, 2009]. A CRYGEP1 (MIM] 123660) pseudogene-reactivating mutation associated with hereditary cataract formation [Brakenhoff et al, 1994] probably also falls into this category.…”
Section: Mutations In Nonprotein-coding Genesmentioning
confidence: 99%
“…The same cleavage of ␥-crystallin between residues Asp 73 and Ser 74 during ␣3 (Ϫ/Ϫ) cataractogenesis is also observed in cases of human cataracts (13). Furthermore, Asp 73 to Gly mutations found in CAT2 mice result in a nuclear cataract (29), and expression of truncated forms of ␥-crystallin is associated with human hereditary Coppock-like cataracts (30). These results suggest that this region within ␥-crystallin is important for maintaining the correct folding and hence the solubility of the protein.…”
Section: 28mentioning
confidence: 99%